VALUE OF PERSONNEL MANAGEMENT IN THE ORGANIZATIONAL MANAGEMENT SYSTEM - Козьмук, Наталія; Власенко, Карина (Socio-economic relations in the digital society, 2019)
The article deals with the functions and tasks of management in general, and personnel in particular, and defines its objectives. It is revealed, that in order to develop, receive profit and keep competitiveness of the organization, the management should optimize return from investments of any resources: material, financial and the main thing — human. It is proved that when an organization really cares about people, its general philosophy, climate and mood necessarily affects the results. It is established that in Ukraine there was a situation where the personnel management is not given enough attention, technology of development and acceptance of personnel decisions is imperfect and scientifically unreasonable, in most cases there is no orientation on achievement of social efficiency in personnel management. Features of management of the personnel of system are lighted. It is revealed that the personnel management system assumes formation of the purposes, functions, organizational structure of management of the personnel, acceptance and realization of administrative decisions. A significant place in the article is occupied by social management, which includes management of labor collective and social structure of the personnel. Creation of social-psychological climate in the team is grounded. At the same time, there is a need to study and establish the importance of personnel management in the organization system. The importance of a favorable psychological climate can be judged, for example, by the fact that a bad mood reduces the efficiency of the team by about one and a half times. Since the circumstances can be influenced purposefully, the psychological climate can be formed and adjusted to some extent. It is also more likely that the psychological state of the team is characterized by the degree of satisfaction of participants with their position. At present, the emphasis on HR management is shifting towards strategic use of employees and measured impact of programs for employees on business.